1980
DOI: 10.1038/283832a0
|View full text |Cite
|
Sign up to set email alerts
|

β-Chain contact sites in the haemoglobin S polymer

Abstract: The amino acid residues involved in the areas of contact that stabilise the haemoglobin S polymer fibre seem to be the same ones that stabilise the basic unit of the deoxyhaemoglobin S crystal: the Wishner-Love double strand. The haemoglobin S fibre is probably formed by a unique packing of these double strands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

1994
1994
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(48 citation statements)
references
References 13 publications
1
47
0
Order By: Relevance
“…On the other hand, only deoxy-HbS generates polymers. As demonstrated by binary mixtures of HbS with Hb mutants (27), the deoxy-HbS fiber has as assembly unit, the Wishner-Love double strand (5,28). This structure requires strong up and down and lateral contacts between tetramers and also between double strands.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, only deoxy-HbS generates polymers. As demonstrated by binary mixtures of HbS with Hb mutants (27), the deoxy-HbS fiber has as assembly unit, the Wishner-Love double strand (5,28). This structure requires strong up and down and lateral contacts between tetramers and also between double strands.…”
Section: Resultsmentioning
confidence: 99%
“…In the current scenario, the definition of a fiber contact by both theoretical as well as experimental approach is centered on specific amino acid residues. The solution studies consider a given residue as a fiber contact only if the mutation of that site results in an altered polymerization behavior relative to the native HbS (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24). On the other hand, the fiber models define a contact residue based on the distance; residues with contact distances of about 5 Å or less are generally considered as interacting partners (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Deoxygenated sickle hemoglobin (HbS) polymerizes into long helical fibers that are believed to be responsible for the pathophysiology of the sickle cell disease. The knowledge gleaned so far from structural analysis of HbS crystal (2)(3)(4), solution polymerization studies of natural variants or engineered mutant hemoglobins (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24), and electron microscopic studies (25) have led to a 14-stranded model of the fiber (26,27). These strands appear as seven double strands of the type found in HbS crystals, albeit with a slight twist caused by fiber packing.…”
mentioning
confidence: 99%
“…The mouse ␣-chain exhibits a very high inhibitory potential against ␤ S -dependent polymerization compared with any other single point mutations of the contact sites of deoxyHbS (3)(4)(5).…”
mentioning
confidence: 99%
“…Inasmuch as solution studies have identified Wishner-Love double strand as the assembly unit of the HbS polymer (3), it is legitimate to use the crystal structure of deoxyHbS to locate intra-double strand contact sites. Sites ␣16, ␣20, ␣23, and ␣116 comply with this characteristic and, in addition, are in spatial proximity despite the fact they are widely separated in the primary sequence (10).…”
mentioning
confidence: 99%